2021
DOI: 10.1016/j.celrep.2021.109767
|View full text |Cite
|
Sign up to set email alerts
|

PHDs/CPT1B/VDAC1 axis regulates long-chain fatty acid oxidation in cardiomyocytes

Abstract: PHDs/CPT1B/VDAC1 axis regulates long-chain fatty acid oxidation in cardiomyocytes Graphical abstract Highlights d Loss of PHD2/3 decreases LCFA uptake and b-oxidation in cardiomyocytes d PHD2/3 bind and prolyl-hydroxylate CPT1B d CPT1B binds to VDAC1, which regulates LCFA metabolism d Hypoxia-insensible CPT1B rescues LCFA metabolism in PHD2/3-deficient cardiomyocytes

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 93 publications
(119 reference statements)
0
10
0
Order By: Relevance
“…As cardiomyocytes mature, the primary mechanism for ATP generation switches from glycolysis to beta fatty acid oxidation (β-FAOX) ( Lopaschuk and Jaswal, 2010 ), which is consistent with our observation that glycolysis genes [Acyl-CoA Synthetase Short Chain Family Member 2 (ACSS2), Glucose-6-Phosphate Isomerase (GPI), and Hexokinase 1 (HK1) ( Glycolysis, 2021 )] were highly expressed in the CM8 cluster (i.e., fetal cardiomyocytes) but not in CM9 (i.e., the CTL-P56–exclusive cluster), while genes involved in β-FAOX [ATP Binding Cassette Subfamily D Member 1 (ABCD1) ( van Roermund et al, 2011 ), Carnitine Palmitoyltransferase 1B (CPT1B) ( Angelini et al, 2021 ), and Hydroxyacyl-CoA Dehydrogenase Trifunctional Multienzyme Complex Subunits Alpha ( Miklas et al, 2019 ) and Beta ( Sekine et al, 2021 ) (HADHA and HADHB, respectively)] were downregulated in CM8 and upregulated in CM9 ( Figures 4A, B ). Sparse-model analysis indicated that glycolysis ( Glycolysis, 2021 ) was the dominant metabolic pathway in most other cardiomyocyte clusters.…”
Section: Resultsmentioning
confidence: 99%
“…As cardiomyocytes mature, the primary mechanism for ATP generation switches from glycolysis to beta fatty acid oxidation (β-FAOX) ( Lopaschuk and Jaswal, 2010 ), which is consistent with our observation that glycolysis genes [Acyl-CoA Synthetase Short Chain Family Member 2 (ACSS2), Glucose-6-Phosphate Isomerase (GPI), and Hexokinase 1 (HK1) ( Glycolysis, 2021 )] were highly expressed in the CM8 cluster (i.e., fetal cardiomyocytes) but not in CM9 (i.e., the CTL-P56–exclusive cluster), while genes involved in β-FAOX [ATP Binding Cassette Subfamily D Member 1 (ABCD1) ( van Roermund et al, 2011 ), Carnitine Palmitoyltransferase 1B (CPT1B) ( Angelini et al, 2021 ), and Hydroxyacyl-CoA Dehydrogenase Trifunctional Multienzyme Complex Subunits Alpha ( Miklas et al, 2019 ) and Beta ( Sekine et al, 2021 ) (HADHA and HADHB, respectively)] were downregulated in CM8 and upregulated in CM9 ( Figures 4A, B ). Sparse-model analysis indicated that glycolysis ( Glycolysis, 2021 ) was the dominant metabolic pathway in most other cardiomyocyte clusters.…”
Section: Resultsmentioning
confidence: 99%
“…However, western blot analysis showed that only CPT1B was suppressed at the protein level by UA stimulation. CPT1B is the rate-limiting enzyme in cardiomyocytes that mediates FA transport into mitochondria for oxidation ( Wang et al, 2020 ; Angelini et al, 2021 ). Therefore, our results suggest that UA may induce FA metabolic disorders via CPT1B-mediated mitochondrial transport.…”
Section: Discussionmentioning
confidence: 99%
“…The dominant carnitine O-palmitoyltransferase (CPT) isoform in the heart is CPT1b. It is located on the outer mitochondrial membrane and catalyses carnitine conjugation of long-chain fatty acids, which facilitates mitochondrial transport and β-oxidation in cardiomyocytes [22]. In a rat diabetes model, CPT1b expression in myocardial tissues was significantly increased compared Liver and kidney Otsuka long-evans tokushima fatty rats, rats with induced insulin resistance Inhibit oxidative stress [30,31] with that in nondiabetic controls.…”
Section: Sglt2i and Myocardial Fat Metabolismmentioning
confidence: 99%